In vitro antimicrobial activity of 20 selected climber species from the Bignoniaceae family - Torres, Carola Analía (2013)
Hydroalcoholic and aqueous extracts of some climber species from the Bignoniaceae family that grow in the north of Argentina were evaluated for in vitro antibacterial activity against Gram-positive and Gram-negative strains. By means of bioautography and disc diffusion methods, it could be determined that all infusions were not active, whereas the hydroalcoholic extracts of seven species were able to inhibit bacterial growth. The minimum inhibitory concentration and minimum bactericidal concentration observed were between 62.5 and 1000 mg gallic acid equivalent (GAE)/mL and between 125 and 1000mg GAE/mL, respectively. The tested extracts were more active against Gram-positive microorganisms. Time-kill experiments indicated that all extracts have bacteriostatic activity. Phytochemical screening showed the presence of terpenoids, phenols and flavonoids. The amount of phenolic compounds and flavonoids was higher in tinctures when compared with infusions. These results suggest the presence of antibacterial substances in the hydroalcoholic extracts, which could be used for the treatment of infections.